ERCC6L-mediated stabilization of HIF-1α enhances glycolysis and stemness properties of lung adenocarcinoma cells - Zhimin Lu; Xuming Yao; Jialu Jiang; Guoxin Hou (Cell Death and Disease)
Abstract Molecular signatures are increasingly recognized as pivotal factors in therapy selection for lung adenocarcinomas (LUAD). A developing therapeutic approach focuses on targeting metabolic dependencies within cancer cells. ERCC6L, a vital protein involved in chromosome separation during cell mitosis, emerges as a compelling subject concerning its impact on LUAD tumorigenesis and progression. Our investigation uncovered elevated levels of ERCC6L in LUAD, significantly associated with unfavorable patient outcomes. Functional analyses elucidate ERCC6L’s role in promoting LUAD cell proliferation, migration, and invasion by inducing glycolysis and stemness characteristics. Mechanistically, our data reveal ERCC6L’s involvement in upregulating aerobic glycolysis through the induction of hypoxia-inducible factor-1α (HIF-1α) expression and transcriptional activity in LUAD cells. Furthermore, ERCC6L stabilizes HIF-1α by inhibiting its hydroxylation and ubiquitin-mediated degradation. The ERCC6L/HIF-1α axis plays a crucial functional role in enhancing cancer stemness and LUAD progression both in vitro and in vivo. Hence, our findings underscore the significance of the ERCC6L/HIF-1α axis in regulating aerobic glycolysis in LUAD cells, suggesting its potential as a biomarker and therapeutic target for LUAD patients.